2011
DOI: 10.1017/s1751731111000607
|View full text |Cite
|
Sign up to set email alerts
|

Length of concentrate finishing affects the fatty acid composition of grass-fed and genetically lean beef: an emphasis on trans-18:1 and conjugated linoleic acid profiles

Abstract: Intensively finishing cattle on a high-grain diet is generally used to enhance marbling, whereas extensively finishing on grass is known to provide improved muscle fatty acid profiles. The objective of this study was to evaluate to what extent intensive concentrate finishing (0, 1 or 2 months) can be combined with forage feeding without negatively affecting the fatty acid profile of genetically lean animals. Bulls from the ‘Asturiana de los Valles’ breed were reared under grazing conditions with/without final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
47
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 59 publications
15
47
1
1
Order By: Relevance
“…Similarly, Klee et al (2011) found higher n-6:n-3 ratios in tenderloin and round cuts from steers fed on pasture plus oat grain than in those cuts from steers fed only on pasture. Aldai et al (2011) reported lower n-6:n-3 ratios in beef from steers finished on pasture than from those fed on intensive grains (primarily barley). Additionally, the highest n-6:n-3 ratio was found in beef from steers fed grain for two months compared with one month.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Klee et al (2011) found higher n-6:n-3 ratios in tenderloin and round cuts from steers fed on pasture plus oat grain than in those cuts from steers fed only on pasture. Aldai et al (2011) reported lower n-6:n-3 ratios in beef from steers finished on pasture than from those fed on intensive grains (primarily barley). Additionally, the highest n-6:n-3 ratio was found in beef from steers fed grain for two months compared with one month.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 96%
“…The percentages of C18:0, CLA c-9 t-11, C18:3 n-3, C20:5 n-3, and C22:5 n-3 were higher for beef from the SW than from the LW treatment (P≤0.05), whereas there were no differences between the oat treatments. Aldai et al (2011) reported that beef from steers finished for two months on grains (primarily barley) had similar levels of CLA c-9 t-11, C20:5 n-3, and C22:5 n-3 but a lower level of C18:3 n-3 than beef finished for one month on grains. Aldai et al (2012) highlighted that the concentrations of fiber and starch in the rumen affected the fatty acid metabolism.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 99%
“…Recent investigations have identified mRNA encoding the elongase and desaturase responsible in bovine tissues (Cherfaoui et al, 2012). Concentrates rich in 18:2n-6 result in higher concentrations of 18:2n-6 and associated longer-chain derivatives in the muscle of cattle (Warren et al, 2008;Aldai et al, 2011;Juá rez et al, 2011) and sheep (Nuernberg et al, 2005;Radunz et al, 2009;Turner et al, 2012a).…”
Section: Altering the Fatty Acid Composition Of Ruminant Meatmentioning
confidence: 99%
“…finishing on high-concentrate diets, rearing of cattle or lambs on forage-based systems is often associated with a decrease in muscle 16:0 and total SFA and higher cis-9 18:1 concentrations Sinclair, 2007;Alfaia et al, 2009;Aldai et al, 2011). Replacing grass silage with wholecrop wheat silage (Noci et al, 2005b) or maize silage ) increased in the n-6 : n-3 ratio of muscle, whereas wilting grass before ensiling decreased this ratio (Noci et al, 2007b).…”
mentioning
confidence: 99%
“…No hubo diferencias en contenido de ácido linoleico (Tabla 3), distinto a lo publicado por otros reportes científicos, donde se observó, que el porcentaje de linoleico en animales alimentados con pastura y forrajes fue el segundo más abundante después del oleico (21). Además el forraje es una fuente importante de linoleico, lo que influye en el contenido del mismo en carne.…”
Section: Discussionunclassified